The Effect of Plyometric Training on the Improvement of Sabit Kick Speed in Pencak Silat Athletes at SMA Negeri 2 Sinjai - Sudirman; Muhammad Qasash Hasyim (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to analyze the effect of plyometric training on the speed of the sabit kick in pencak silat athletes at SMA Negeri 2 Sinjai, using a quantitative approach and experimental design. In this study, 10 students involved in pencak silat extracurricular activities were selected as samples, and data were collected through pre-test and post-test measurements of the speed of the sabit kick. The results of the study showed a decrease in the average kick speed from 1.45 seconds in the pre-test to 1.30 seconds in the post-test, indicating an increase in kick speed after the implementation of plyometric training. Additionally, correlation analysis found that lower body strength and agility significantly contributed to the improvement in sabit kick speed, consistent with the theory that plyometric training can enhance muscle power and agility, two key factors in pencak silat. These findings confirm previous research indicating that plyometric training positively influences movement speed in martial arts. Overall, the results of this study provide strong evidence that plyometric training can improve the speed of the sabit kick in pencak silat athletes, and it is recommended that plyometric training be integrated into physical training programs for pencak silat. However, further research with a larger sample size and additional variables such as kicking techniques and psychological factors is needed to gain a more comprehensive understanding of the factors influencing kicking speed in pencak silat.